2006
DOI: 10.1158/1535-7163.mct-06-0457
|View full text |Cite
|
Sign up to set email alerts
|

Terbinafine inhibits endothelial cell migration through suppression of the Rho-mediated pathway

Abstract: We showed previously that terbinafine, an allylamine with fungicidal activity, could inhibit angiogenesis by suppressing the endothelial cell proliferation. In the present study, we further showed that terbinafine (0 -120 Mmol/L) dose dependently inhibited the adhesion and migration of human umbilical vascular endothelial cells (HUVEC). Western blot analysis showed that terbinafine decreased the levels of Ras protein and membrane-bound RhoA protein. Moreover, the terbinafine-induced migration inhibition in HUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Overall, our results indicated that hESC-derived ECs mature under flow conditions, as shown by the up-regulation of the mechanosensory complex and their capacity to express HSPG. ) conditions can respond to compounds that interfere with EC activity, we cultured cells for 7 d in each condition, after which the culture medium was supplemented or not with terbinafine (0.1 and 1 μM), an antiangiogenic drug that suppresses EC proliferation and activates EC apoptosis (17,18), for an additional day. Our results indicated that the hESC-derived ECs are highly sensitive to terbinafine because the expression of inflammation (ICAM-1; E-SELECTIN), oxidative stress sensing (HO-1), and vasculature modulation (eNOS) genes was upregulated in cells cultured in flow conditions with terbinafine (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our results indicated that hESC-derived ECs mature under flow conditions, as shown by the up-regulation of the mechanosensory complex and their capacity to express HSPG. ) conditions can respond to compounds that interfere with EC activity, we cultured cells for 7 d in each condition, after which the culture medium was supplemented or not with terbinafine (0.1 and 1 μM), an antiangiogenic drug that suppresses EC proliferation and activates EC apoptosis (17,18), for an additional day. Our results indicated that the hESC-derived ECs are highly sensitive to terbinafine because the expression of inflammation (ICAM-1; E-SELECTIN), oxidative stress sensing (HO-1), and vasculature modulation (eNOS) genes was upregulated in cells cultured in flow conditions with terbinafine (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RhoA is required for cell motility in response to some stimuli (3,26,65), including strain (98) in other cells, and RhoA-dependent, ROCK-dependent signaling is required for epithelial migration across nondeforming substrates (62,68,76), including intestinal IEC-6 and T84 cells (60). Others have also observed that inhibiting RhoA or ROCK can stimulate basal migration (15,40,58,77,86,89) while blocking the stimulation of migration by some other stimulus in other cells (36,39,94). In our hands, silencing mDia1 also enhanced basal migration across tissue fibronectin similarly to ROCK inhibition or reduction while preventing strain stimulation of migration.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as described previously [27]. Briefly, cell lysates were prepared, electrotransferred, immunoblotted with antibodies, and then visualized by incubating with the enhanced chemiluminescence system (Amersham, Buckinghamshire, England).…”
Section: Methodsmentioning
confidence: 99%